Lateglacial to Holocene climatic and environmental changes in Europe : multi-proxy studies on lake sediments along a transect from northern Italy to northeastern Poland - Lauterbach, Stefan (2012)
Sediment records of three European lakes were investigated in order to reconstruct the regional climate development during the Lateglacial and Holocene, to investigate the response of local ecosystems to climatic fluctuations and human impact and to relate regional peculiarities of past climate development to climatic changes on a larger spatial scale. The Lake Hańcza (NE Poland) sediment record was studied with a focus on reconstructing the early Holocene climate development and identifying possible differences to Western Europe. Following the initial Holocene climatic improvement, a further climatic improvement occurred between 10 000 and 9000 cal. a BP. Apparently, relatively cold and dry climate conditions persisted in NE Poland during the first ca. 1500 years of the Holocene, most likely due to a specific regional atmospheric circulation pattern. Prevailing anticyclonic circulation linked to a high-pressure cell above the remaining Scandinavian Ice Sheet (SIS) might have blocked the eastward propagation of warm and moist Westerlies and thus attenuated the early Holocene climatic amelioration in this region until the final decay of the SIS, a pattern different from climate development in Western Europe. The Lateglacial sediment record of Lake Mondsee (Upper Austria) was investigated in order to study the regional climate development and the environmental response to rapid climatic fluctuations. While the temperature rise and environmental response at the onset of the Holocene took place quasi-synchronously, major leads and lags in proxy responses characterize the onset of the Lateglacial Interstadial. In particular, the spread of coniferous woodlands and the reduction of detrital flux lagged the initial Lateglacial warming by ca. 500–750 years. Major cooling at the onset of the Younger Dryas took place synchronously with a change in vegetation, while the increase of detrital matter flux was delayed by about 150–300 years. Complex proxy responses are also detected for short-term Lateglacial climatic ...